Evaluasi Kebijakan Peraturan Walikota Tanjungpinang Nomor 14 Tahun 2022 Tentang Pengurangan Penggunaan Kantong Plastik : (Studi Kasus Kota Tanjungpinang) - M. Taufik Ar Rauf; Fitri Kurnianingsih; Firman Firman (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Garbage is a problem that often occurs everywhere. One example is in Tanjungpinang City with various types of waste problems, one of which is plastic waste. For this reason, it needs to be handled seriously. One of the measures that has been carried out by the Tanjungpinang City government regarding the handling of plastic waste is to create a Tanjungpinang Mayor regulation policy no. 14 of 2022 concerning reducing the use of plastic bags. This regulatory policy was implemented on July 7 2022 and the policy of this regulation has been in place for approximately 2 years now. However, the results of implementing this policy regulation are still not as expected, with the data that has been presented in the background proving that every year there is an increase and plastic waste is in second place among the number of types of waste that exist. For this reason, this research aims to evaluate all forms of activities in implementing this policy using a descriptive qualitative approach according to the evaluation theory of Abdulkahar Badjuri & Teguh Yuwono (2002) which consists of 4 indicators, namely: suitability evaluation, effectiveness evaluation, efficiency evaluation and meta evaluation. Based on this theory, this research hopes that in the future this problem can be resolved and that regulatory policies run as expected so as to produce the desired results.